Table grape water requirements in the submedium São Francisco Region - Netto, Jaqueline Ávila; Azevedo, Pedro Vieira de; Silva, Bernardo Barbosa da; Soares, José Monteiro; Teixeira, Antonio Heriberto de Castro (Pesquisa Agropecuaria Brasileira, 2000)
This study used data of a field experiment conducted at the Bebedouro experimental base of the Embrapa-Centro de Pesquisa Agropecuária do Trópico Semi-Árido in Petrolina, PE, Brazil, from May to August, 1996, during the growing period of a five-year-old table grape (Vitis vinifera L.), Italy cultivar. The plants were conducted in a two-meter above soil surface trellis system, four meters between rows by two meters between plants, and daily irrigated by trickling system. The crop evapotranspiration was determined by the soil water balance method, and the reference evapotranspiration was estimated by the method of Penman, used to analyse the behaviour of the crop coefficient (Kc) throughout the crop growing period. The maximum crop daily water use was 4.33 mm d-1 and the total water consumption was 333.6 mm for the whole growing period. The crop coefficient values varied from 0.50 to 0.74. A characteristic curve of Kc for the table grape vegetative cycle was obtained which allows to obtain daily values of Kc as a function of days after pruning.
Keywords: Vitis vinifera; plant water relations; water balance; evapotranspiration; trickle irrigation; water use